Pengaruh Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Pada Sektor Perbankan - ayu_widia_pasha; Riany, Meutia (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the influence of the Accounting Information System (AIS) on the quality of financial statements in the banking sector, specifically focusing on the timeliness dimension. Amidst high demands for transparency, the banking sector often faces constraints in complex financial data management and the risk of reporting delays. This research employs a quantitative approach with a sample of six banks over the 2021-2024 period. Data analysis techniques involve linear regression to test the impact of AIS investment and firm size on the duration of financial statement presentation. The results indicate that at a 90% confidence level (α = 10%), investment in the Accounting Information System has a significant effect on accelerating the timeliness of financial reporting. This is evidenced by a negative coefficient of -3.172, indicating that an increase in AIS quality effectively reduces reporting lags. Furthermore, firm size was also found to have a significant influence on reporting efficiency at the same significance level. These findings confirm that automation through AIS and adequate asset scale are key factors in maintaining the relevance of accounting information and mitigating the risk of sanctions from financial service authorities.